ANALISIS PROMOSI JABATAN, KOMPENSASI DAN LINGKUNGAN KERJA DALAM MENINGKATKAN MOTIVASI KERJA KARYAWAN DI KOPERASI KONSUMEN BMT BINA UMMAT MADANI BANYUASIN - Ikhwan, Afiful; Porwani, Sri; Kurniati, Echi; Ridho, Ahmad Muhammad (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This look at targets to investigate task promoting, reimbursement and work surroundings in growing worker motivation in BMT Bina Ummat Madani Banyuasin client Cooperative. The sampling approach used is a saturated sampling method, particularly all personnel of BMT Bina Ummat Madani Banyuasin client Cooperative, a complete of 21 respondents. This study employs a quantitative methodology featuring descriptive analysis. The consequences showed that process advertising, reimbursement and paintings environment had been best in increasing worker motivation. this could be visible from the results of the percentage of respondents regarding task promotion with a percent degree of ninety eight%, reimbursement with a percentage degree of 86% and paintings environment with a percent degree of 78%.